Designing Jakarta Halal Tourism Application with Collaborative and Location-Based Filtering Method as Jakarta Smart City Optimization (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2023)
Jakarta is one of the Muslim-friendly tourist destinations in Indonesia. The DKI Jakarta government has various limitations in managing existing facilities, so community participation is needed. It encourages people to utilize application-based new media to answer the challenges and problems faced by Jakarta. A platform is required in the form of a digital application that can load destinations ranging from places, lodging, food, and facilities owned by tourist attractions labeled halal tourism to make it easier to find halal tourist destinations in Jakarta as an optimization of intelligent cities and contribute to SDGs. Halal tourism applications make it easier for people to get information related to Halal Tourism in Jakarta with the most popular development methods, namely collaborative filtering and location-based filtering methods. This method uses knowledge gathered from monitoring the behavior and personal choices of system users, who are generally known as personal profile users. The research method used is Research and Development (R&D) by designing an Android-based system. Data collection is an interview with sources with the DKI Jakarta Tourism and Creative Economy Office accompanied by expert information. The result of this research is the design of the Jakarta City Halal Tourism Application (SI PAHAJI) aimed at local and foreign tourists. The application contains information about tourist attractions, accommodations, and other facilities that are friendly to halal visitors in DKI Jakarta to help recommend tourist destinations in DKI Jakarta that follow user preferences and locations.